New Student Admission Selection System at PTKIN: Effectiveness of Entrance Pathways and its Relationship with Grade Point Average - Mohamad Erihadiana; Undang Syaripudin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study examines the selection system for new student admissions at Islamic Religious Universities in Indonesia and its correlation with students' Grade Point Average (GPA) in UIN Sunan Gunung Djati Bandung, UIN Sunan Ampel Surabaya, UIN Walisongo Semarang. This research adopts a mixed-methods approach, integrating both quantitative and qualitative analyses. The quantitative analysis utilizes correlation techniques and descriptive statistics to examine relationships within the data. Meanwhile, the qualitative analysis employs content analysis of policies and documents, complemented by in-depth interviews with election officials and a comprehensive literature review, to investigate the transparency and efficiency of the selection system. Findings reveal no significant correlation between the specific admission pathway and the student's GPA. This suggests that the existing selection system is equally effective across different entry channels in predicting academic success as measured by GPA. The study underscores the importance of maintaining transparent, inclusive, and accountable admission processes, enhancing public trust in Islamic Religious Universities. The research contributes insights into optimizing student selection processes to align with educational goals and uphold academic standards.